Case reportBloch-Sulzberger syndrome: a case report - Rosińska-Więckowicz, Anna; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Incontinentia pigmenti (IP, Bloch-Sulzberger syndrome) is a very rare genodermatosis characterized by typical skin lesions accompanied by dental, central nervous system, bone and ocular abnormalities. Incontinentia pigmenti is usually observed among women, as this X-linked dominantly inherited disorder is lethal in males. The hallmark feature of IP is cutaneous eruption along the lines of Blaschko, usually accompanied by neurological disorders. Apart from clinical features of the disease, skin biopsy is the best diagnostic tool to confirm the diagnosis. We present a case of a newborn with typical vesicular and then verrucous lesions affecting the lower legs.